Investigating Dissertation Supervisors' Characteristics Valued by Supervisees and their Effect on the Supervision Process - Bekki Chaima; Bouchama-Sari Ahmed Fizya (Babes-Bolyai University, 2024)
The Supervision process requires both supervisors and supervisees to perceive supervisors' qualities as a determining criterion in the selection of supervisors. In order to investigate supervisors' characteristics valued by supervisees and their effect on the supervision process in the English department at the University of Tiaret, two questionnaires were handed to 40 Master 2 Didactic students and 10 teachers selected through purposive sampling The data generated were subject to quantitative and qualitative analysis. The findings revealed that supervisees appreciate supportive, flexible, responsive, available and knowledgeable supervisors. Results also suggested that directive, demanding, unresponsive and inaccessible supervisors are not appreciated. Further, it was found that lack of clear guidelines on how to choose a good supervisor, lack of awareness of the roles of supervisors and supervisees and obliviousness of supervisors' contribution to supervisees' overall development were the principal reasons causing challenges in finding a suitable supervisor. The findings also showed that supervisors' selected characteristics enhance supervision by creating an inclusive and productive environment that reaches intended outcomes efficiently. Considering these results, the following pedagogical implications are offered. The study argues for organizing seminars to inform (future) supervisees of characteristics of good supervisors and how to choose a suitable one, cultivating a positive relationship between supervisors and supervisees by clarifying the roles of each, scheduling meetings between supervisors and supervisees to create a code of conduct for working together on long terms, regulating guidelines for supervisor selection and tailoring supervisory programs that prioritize the characteristics identified in this research.